Suppression model of energy sink-hole attack in WSN based on the unequal cluster radius and mobile cluster head - Wei-wei ZHOU; Bin YU (Tongxin xuebao)
To overcome the problem that partial cluster heads were drastically exhausted by the energy sink-hole attack in wireless sensor network,a novel suppression model based on the optimal path of mobile cluster heads was proposed,which was shown to balance the energy consumption in each cluster head.With the adoption of unequal cluster radius and data traffic monitoring explicitly,the inhibition mechanism was modeled as multivariate linear equations.Furthermore,toroidal projection was adopted to calculate the Euclidean distance,based on which the initial energy of mobile cluster head was configured correspondingly.On this basis,an algorithm based on the minimum cluster lifetime and throughput threshold was provided to achieve the detection and suppression of energy sink-hole attack.The experimental results show that the developed algorithm can suppress energy sink-hole attack evidently and efficiently and is suitable to the resource constrained WSN.